The Effectiveness of Gratification Arrangements as Part of Corruption Crimes in Indonesia: A Theoretical Study in Talcott Parsons Perspective - Asmara, Teddy (International Journal of Criminology and Sociology, 2021)
This research aims to examine the crime of gratification as part of the criminal act of corruption, which will be seen in Talcott Parson's perspective. Corruption today is a problem for developing countries and has become a world problem that requires integral and transnational handling. One of the most disclosed forms of corruption today is corruption in the form of gratuities. This research method uses normative juridical research with the approach of laws, concepts, and principles and collects primary legal material in the form of Law 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption Crimes. The results of this study found that the Cybernetics Theory, which Talcott Parsons coined, views the problem of alleged gratification as being strongly influenced by the economic sub-system, this is because a decision that is made has a significant impact on anyone, so it is not surprising if there is a lot of price bargaining. Moreover, the least impact is the cultural sub-system because this sub-system is only the economic sub-system's impact.